Difference and subordination – the epistemic struggles of collaborative knowledge production in the field of mental health - Jenny Ziegenhagen; Ute Maria Krämer; Georgia Fehler; Guillermo Ruiz Perez; Daniela Schmidt; Lauren Cubellis; Madeleine Küsel; Sebastian von Peter (Research Involvement and Engagement)
Abstract Background Collaborative or co-productive approaches in the field of mental health care research are often legitimized by the argument that researchers with lived experience of mental health crisis and disability (= LE) produce different knowledge as compared to those without these experiences At the same time, there is a lack of studies that report on the underlying collaborative processes and on how these processes affect the knowledge that is being produced. This manuscript describes a collaborative research process and how this process impacted the knowledge produced. Methods The collaborative research process entailed a multi-step coding process, using a variant of thematic analysis. To facilitate comparison, two code systems were produced, one by researchers with and the other by researchers without LE of mental health crisis and disability. Subsequently, the code systems of these two sub-teams were integrated into a single code system. To evaluate the potential differences between the code formations of the two sub-teams as well as the effects of their integration, three focus groups suceeded, composed of 1) psychology students as well as researchers 2) with and 3) without LE, whose results are at the core of this manuscript. Results The focus group participants described extensive differences between the code formation of the researchers with and without LE – first in form, but also more substantially in the contents of both systems – corresponding to two distinct logics for understanding the implementation of PSW: an “institutional” and “interactional” logic. The integration process of both code systems was described as invasive, resulting in a final code system that more closely resembled the primary code system of the researchers without LE. Conclusion The distinct logic of the two code systems can be thought of as distinct but complementary positions on the topic of PSW implementation. Such an explanation, however, falls short, as it silences the power relations and diverging interests and positions of the researchers involved. This is supported by what resulted from the integration of both code systems, resulting in the continuation of the logic of the researchers without LE. It is concluded that epistemic struggles and their knowledge politics require greater attention in the context of collaborative mental health research.